Hematopoietic Stem/Progenitor Cells Express Several Functional Sex Hormone Receptors—Novel Evidence for a Potential Developmental Link Between Hematopoiesis and Primordial Germ Cells - Mierzejewska, Katarzyna (Stem Cells Dev, 2015)
Evidence has accumulated that hematopoietic stem progenitor cells (HSPCs) share several markers with the germline, a connection supported by reports that prolactin, androgens, and estrogens stimulate hematopoiesis. To address this issue more directly, we tested the expression of receptors for pituitary-derived hormones, such as follicle-stimulating hormone (FSH) and luteinizing hormone (LH), on purified murine bone marrow (BM) cells enriched for HSPCs and tested the functionality of these receptors in ex vivo signal transduction studies and in vitro clonogenic assays. We also tested whether administration of pituitary- and gonad-derived sex hormones (SexHs) increases incorporation of bromodeoxyuridine (BrdU) into HSPCs and expansion of hematopoietic clonogenic progenitors in mice and promotes recovery of blood counts in sublethally irradiated animals. We report for the first time that HSPCs express functional FSH and LH receptors and that both proliferate in vivo and in vitro in response to stimulation by pituitary SexHs. Furthermore, based on our observations that at least some of CD45(−) very small embryonic-like stem cells (VSELs) may become specified into CD45(+) HSPCs, we also evaluated the expression of pituitary and gonadal SexHs receptors on these cells and tested whether these quiescent cells may expand in vivo in response to SexHs administration. We found that VSELs express SexHs receptors and respond in vivo to SexHs stimulation, as evidenced by BrdU accumulation. Since at least some VSELs share several markers characteristic of migrating primordial germ cells and can be specified into HSPCs, this observation sheds new light on the BM stem cell hierarchy.